Women Oppression as A Result of Male Domination Represented in Malladi’s Novel The Mango Season - Asturi, Ratna Dwi; Rosyidi, Mohamad Ikhwan (Allure Journal, 2022)
Oppression is the name of social injustice. It is perpetuated through social institutions, practices, and norms on social group by social group. Indian society belongs to the man since time immemorial. The woman has been given a secondary and inferior position in her family and society. She has been facing injustice, suppression, oppression, subjugation, and exploitation in a male-dominated Indian society. This study aims to describe how male domination and women’s oppression experienced by women and its explanation in what extent oppression reject male domination represented in The Mango Season novel. The method used in this study is descriptive qualitative study and using Derrida’s theory of deconstruction to support the data. The main theory used in this study is Maine’s theory of Patriarchy in a perspective of feminist. This study shows that the novel deconstructs its portrayal of male’s domination towards women. So, by destabilizing the binary opposition in the novel, that are males oppose females, the males-females hierarchy are reversed.